2015
DOI: 10.1016/j.biomaterials.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

ROS-responsive microspheres for on demand antioxidant therapy in a model of diabetic peripheral arterial disease

Abstract: A new microparticle-based delivery system was synthesized from reactive oxygen species (ROS)-responsive poly(propylene sulfide) (PPS) and tested for “on demand” antioxidant therapy. PPS is hydrophobic but undergoes a phase change to become hydrophilic upon oxidation and thus provides a useful platform for ROS-demanded drug release. This platform was tested for delivery of the promising anti-inflammatory and antioxidant therapeutic molecule curcumin, which is currently limited in use in its free form due to poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
123
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 75 publications
0
123
0
1
Order By: Relevance
“…[8][9][10][11][24][25][26][27] It has received extensive attention with its unique effectiveness in glioma therapy. Previous studies demonstrated that Cur can significantly inhibit the proliferation of glioma cells by downregulating multidrug resistance proteins that cause the efflux of many chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][24][25][26][27] It has received extensive attention with its unique effectiveness in glioma therapy. Previous studies demonstrated that Cur can significantly inhibit the proliferation of glioma cells by downregulating multidrug resistance proteins that cause the efflux of many chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the levels of H 2 S in diabetic and deguelintreated rats; deguelin significantly increased H 2 S levels in diabetes-induced rats, suggesting a possible role for H 2 S in activating the antioxidant defence system. A previous study reported involvement of the Nrf2-dependent pathway in the effects of H 2 S against oxidative stress [31]. Therefore, we measured the levels of both HO-1 and Nrf2 in DRG neurons; both were markedly increased in diabetes-induced rats after treatment with deguelin.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, reactive oxygen species (ROS)-responsive microspheres (polypropylene sulfide) loaded with curcumin were delivered to mouse ischemic limbs via intramuscular injection to the gastrocnemius and adductor muscles [116]. Curcumin has been known to exhibit strong antioxidant and anti-inflammatory properties to keep inflammatory cells at bay within wound sites.…”
Section: Efficacy Of Modified Synthetic Hydrogels That Accentuate Heamentioning
confidence: 99%